The effect of film and paper on quality of Cone beam CT image and their diagnostic accuracy in detection of inferior alveolar canal - Ladan Hafezi; Ahmadreza Talaeipour; Bentolhoda Kamali (Tehran University of Medical Sciences, 2017)
Background and Aims: According to the research background and need to print CBCT images in case of emergency, this study has been done to compare the quality and accuracy of the two methods of film and paper printing for CBCT images. Materials and Methods: The study of CBCT images taken from 5 patients was done and the cross-sectional slices on Fotolusio DNP papers and film AGFA were printed. Afterward, the images was exmined by a maxillofacial radiologist. The images’ quality were identified and recorded with anatomical, from 1 to 4 on forms. The accuracy was determined by the diagnosis of alveolar canal area and the comparison with the gold standard. Data were analyzed using independent chi-square and Fisher exact tests’. Results: The images quality in anatomical landmarks consisting PDL (P=0.02), lamina dura (P=0.006), the inferior alveolar canal (P=0.01) and the filling (P=0.006) had a significant difference. There was no significant difference. For the lower border of the mandible landmark, there was no difference between the two methods of printing. In comparing the diagnostic accuracy between the two methods (P=1). Conclusion: The results showed that the diagnostic quality in film printing is better than paper printing and the diagnostic accuracy is the same in both methods.